A review of secondary contamination of drinking water quality in distribution systems: sources, mechanisms, and prospects - Wang, Zhi; Yang, Xiaozhou; Fu, Lei; Li, Manjie (Aqua (London, England), 2025)
Drinking water that complies with established standards at treatment plants inevitably undergoes secondary contamination upon entering distribution systems. A bibliometric analysis highlights the expanding body of research on drinking water distribution systems (DWDSs), emphasizing the paramount importance of safeguarding drinking water quality and mitigating secondary contamination within these networks. This study delves into the sources, health implications, and mitigation strategies pertaining to three predominant forms of secondary contamination, namely metal release, microbial regrowth, and disinfectant by-product (DBP) formation, as well as the intricate interactions among these contaminants. The release of heavy metals is inherently linked to the corrosion process of metallic components of pipelines, which is affected by water quality and hydraulic dynamics. Microbial regrowth within DWDSs is potentially associated with the reproduction of waterborne pathogens, which can lead to significant health outcomes including acute gastroenteritis and diarrhea. Consequently, disinfection is commonly employed to prevent pathogen proliferation in DWDSs, whereas the residual disinfectants can react with natural organic matter or halogen ions in waters, resulting in the formation of DBPs. To mitigate the adverse effects of DBPs, various practical interventions are implemented at distinct stages of water distribution, encompassing source control, process control, and end control.